2010
DOI: 10.1111/j.1365-2141.2010.08316.x
|View full text |Cite
|
Sign up to set email alerts
|

The microenvironment differentially impairs passive and active immunotherapy in chronic lymphocytic leukaemia – CXCR4 antagonists as potential adjuvants for monoclonal antibodies

Abstract: Summary Direct contact with stromal cells protects chronic lymphocytic leukaemia (CLL) B cells from chemotherapy‐induced apoptosis in vitro. Blockade of CXCR4 signalling antagonizes stroma‐mediated interactions and restores CLL chemosensitivity. In vivo, administration of CXCR4 antagonists effectively mobilizes haematopoietic progenitor cells. Therefore, combinations of CXCR4 blockade and cytoreductive treatment with selective activity on CLL cells may avoid potential haematotoxicity. Hence, we tested CXCR4 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…Consistent with previous reports, 50 coculture of Raji cells with M2 10B4 BM stromal cells increased their resistance to rituximab treatment ( Figure 5C). To determine whether the protective effect of M2 10B4 cells could be reversed by blockade of the CXCR4 receptor, Raji cells were treated with vehicle or rituximab (10 g/mL) in the presence or absence of CXCR4 pepducins.…”
Section: Cxcr4 Pepducins Reverse the Protective Effect Of Stroma And supporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with previous reports, 50 coculture of Raji cells with M2 10B4 BM stromal cells increased their resistance to rituximab treatment ( Figure 5C). To determine whether the protective effect of M2 10B4 cells could be reversed by blockade of the CXCR4 receptor, Raji cells were treated with vehicle or rituximab (10 g/mL) in the presence or absence of CXCR4 pepducins.…”
Section: Cxcr4 Pepducins Reverse the Protective Effect Of Stroma And supporting
confidence: 81%
“…All patient CLL B cells tested had high CXCR4 expression levels (data not shown). Both PZ-218 and PZ-210 significantly inhibited cell migration/chemotaxis to CXCL12 with comparable IC 50 Chemotaxis of vehicle-treated cells to CXCL12 was set at 100%, and random chemotaxis (chemotaxis of cells in the absence of CXCL12) was set at 0%. Data are presented as the means Ϯ SEM of triplicate experiments with n ϭ 3 for each experiment.…”
Section: Resultsmentioning
confidence: 99%
“…39,40 This is because microenvironmental signals, including interactions between CLL cells and CD40L-expressing T cells, stromal and nurse-like cells are known to increase the apoptotic threshold of CLL cells. 41,42 CD40-CD40L interactions have been shown to augment the antigen-presenting capacity of CLL cells due to increased surface expression of adhesion molecules (CD54) and co-stimulatory molecules such as CD80, CD86 and CD70 leading to CLL cell activation and protection from fludarabine-mediated killing.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…39,40 This is because microenvironmental signals, including interactions between CLL cells and CD40L-expressing T cells, stromal and nurse-like cells are known to increase the apoptotic threshold of CLL cells.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] The combined use of ibrutinib with anti-CD20 antibodies [7][8][9] or other monoclonal antibodies (mAbs) has been suggested for the treatment of patients with CLL because they use different mechanisms for antileukemia activity. Additionally, we and others have previously shown that microenvironmental interactions protect CLL and lymphoma cells from rituximab-induced cytotoxicity [10][11][12] and chemotherapyinduced apoptosis. 11,13 The ibrutinib-induced lymphocytosis suggests that a combinatorial therapy with mAbs might overcome adhesionmediated antibody resistance and synergize with anti-CD20 mAbs.…”
Section: Introductionmentioning
confidence: 99%